2016
DOI: 10.1208/s12249-016-0673-1
|View full text |Cite
|
Sign up to set email alerts
|

Design of Magnetic Polymeric Particles as a Stimulus-Responsive System for Gastric Antimicrobial Therapy

Abstract: The treatment of peptic ulcers induced by H. pylori remains challenging due to the deep mucous layer location of bacteria preventing antimicrobial drug access. The present work aimed to design and evaluate in vitro dual responsive (both pH and magnetic field-sensitive) polymeric magnetic particles loaded with amoxicillin as a smart drug carrier for deep mucous layer penetration and in situ drug release. Magnetite particles were produced by the co-precipitation method and subsequently coated with the EudragitS1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 50 publications
(11 reference statements)
0
8
0
Order By: Relevance
“…A dual pH- and magnetic field-responsive magnetite coated with Eudragit ® S100 was fabricated and loaded with amoxicillin. In vitro studies demonstrated its usefulness as an antibacterial agent [ 188 ].…”
Section: Stimuli-responsive Polymeric Nanocarriers For Drug and Gmentioning
confidence: 99%
“…A dual pH- and magnetic field-responsive magnetite coated with Eudragit ® S100 was fabricated and loaded with amoxicillin. In vitro studies demonstrated its usefulness as an antibacterial agent [ 188 ].…”
Section: Stimuli-responsive Polymeric Nanocarriers For Drug and Gmentioning
confidence: 99%
“…Hybrid strategies for targeting the IME include, dual endogenous stimuli-responsive nanosystems (pH/enzyme) 55,56 and endo/exogeneous stimuli-responsive nano-systems, which utilize pH/magnetic 53 , pH/PTT 61 , enzyme/PTT 67 and enzyme/US 69 triggers. The codelivery of an antibiotic and an anti-inflammatory agent to the site of infection was proposed as a novel strategy for sepsis therapy, to diminish the bacteria and the inflammation response simultaneously.…”
Section: Complex Hybrid Triggered Nano-systemsmentioning
confidence: 99%
“…Since not all implants are conductive, the alternative utilization of magnetic field and pH activation proposed in ref. [181] can be also considered as the very perspective way. Finally, the combination of other stimuli, like light and supramolecular host-guest chemical interaction, was also reported [182], and further progress in this field can be expected.…”
Section: Physico-chemical Stimulationmentioning
confidence: 99%